Hendra in the Hunter Valley - K.M. Williamson; S. Wheeler; J. Kerr; J. Bennett; P. Freeman; J. Kohlhagen; A.J. Peel; P. Eby; T. Merritt; T. Housen; C. Dalton; D.N. Durrheim; et al. (One Health, 2020)
In June 2019 the first equine case of Hendra virus in the Hunter Valley, New South Wales, Australia was detected. An urgent human and animal health response took place, involving biosecurity measures, contact tracing, promotion of equine vaccinations and investigation of flying fox activity in the area.No human or additional animal cases occurred. Equine vaccination uptake increased by over 30-fold in the surrounding region in the three months following the case. Black flying fox and grey-headed flying fox species were detected in the Valley. The incident prompted review of Hendra virus resources at local and national levels.This event near the “horse capital of Australia”, is the southernmost known equine Hendra case. Management of the event was facilitated by interagency collaboration involving human and animal health experts. Ongoing One Health partnerships are essential for successful responses to future zoonotic events.